(untitled) (Baghdad Science Journal, 2025)
Some parameters for advancement of Leishmania tropica infection were examined in three groups of golden hamsters, Group (1) inoculated with autoclaved killed Leishmania tropica , Group (2) inoculated with BCG vaccine alone while Group (3) Inoculated with mixed vaccine (autoclaved killed Leishmania with BCG). The follow up of experimentally infected animals with virulent isolation of Leishmania tropica was done for 90 days, the animals inoculated with mixed vaccine (autoclaved killed Leishmania with BCG) showed the minimum average in each of foot pad thickness (2.3 ± 0.05) mm after (60) days of infection, spleen enlargement (1.13±0.38) after (45) days of infection, spleen length (23.9±0.08) mm after (30) days of infection, liver weight(3.8±0.52) gm after (90) days of infection and estimated number of parasites in the spleen (0.91±0.04) million parasites after (30) days of infection. In conclusion, the mixed vaccine was effective to protect animals against subsequent infections which may cause lesions, and minimized the number of parasites in spleen for (90) days after infection.